Types of leisure time physical activities (LTPA) of community-dwelling persons who have been screened positive for dementia - Britta Müller; Peter Kropp; Maria Isabel Cardona; Bernhard Michalowsky; Nanja van den Berg; Stefan Teipel; Wolfgang Hoffmann; Jochen René Thyrian (BMC Geriatrics, 2021)
Abstract Background To (a) describe the pattern of leisure time physical activities (LTPA) in community-dwelling persons who have been screened positive for dementia and (b) determine the health-related and sociodemographic factors associated with LTPA. Methods Data of the general practitioner-based, randomized, controlled intervention trial, DelpHi-MV (Dementia: life- and person-centered help in Mecklenburg-Western Pomerania) were used. Patients aged 70 years or older, who lived at home and had a DemTect< 9 were informed about the study by their General practitioners and invited to participate. Data from 436 participants with complete baseline data were used. Standardized, computer-assisted assessments were made during face-to-face interviews at the participants’ homes. Results Two hundred thirty-eight patients (54.6%) carried out LTPA (men 58.4%, women 51.8%). Physically active patients mentioned one to two different activities; diversity of LTPA was higher for men than for women. The most-frequently mentioned types of activity were gardening (35.3%), cycling (24.1%) and mobility training (12.4%); there was only a statistically significant difference between men and women in cycling, χ2(1) = 21.47, p < .001. The odds of LTPA increased with increasing quality of life (OR = 2.41), lower impairments in activities of daily living (OR = 0.85), and living in a rural environment (OR = 2.02). Conclusions Our findings suggest that people who have been screened positive for dementia living in a rural area are more likely to be active than people living in an urban area. Following studies should investigate whether this difference has an effect on the progression of dementia. Trial registration ClinicalTrial.gov Identifier NCT01401582 .